Peran Saksi dalam Kehakiman Islam pada Kitab Alfiyyah Zubad pada Mata Pelajaran Kitab di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: The Role of Witnesses in Islamic Justice in the Alfiyyah Zubad Book in Book Subjects at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - Muhammad Halim Fatahillah; Farih Zacky Al Gozali; Dony Fajar Alfiyanto; Rahmad Setio Egi Cahyono (Litera Academica Publishing, 2025)
This study discusses the role of witnesses in the Islamic judicial system based on the book Alfiyyah Zubad by Imam Ahmad bin Ruslan al-Syafi'i and its implementation in learning at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta. In Islamic law, testimony (syahadah) plays a crucial role as the primary tool for upholding justice, while also reflecting honesty and moral integrity. In Alfiyyah Zubad, witnesses not only convey legal information but also serve as guardians of social morality. Sheikh Ahmad bin Ruslan emphasized the requirements for a witness, such as being just, sane, not wicked, and having a good moral reputation, so that testimony encompasses legal, ethical, and spiritual aspects. This study uses a qualitative approach with a descriptive-analytical method. Data were obtained through the study of classical books (turats), observations of Alfiyyah Zubad learning at the Islamic boarding school, and interviews with caregivers and senior students. The results show that learning the book not only emphasizes understanding legal texts but also shapes the character and integrity of students so that they are morally responsible in social life. Testimonial values ​​such as honesty, trustworthiness, and justice are incorporated into moral education in Islamic boarding schools. Thus, the concept of witness in Alfiyyah Zubad is relevant to contemporary Islamic legal education. Islamic boarding schools play a crucial role in instilling legal ethics through the study of classical texts that are both textual and applicable, enabling students not only to understand the law but also to practice it in real life.